Islamic Criminal Law Analysis of Cyber Crimes on Consumers In E-Commerce Transactions - Jaenudin Jaenudin; Rasyida Rofiatun Nisa (Green Publisher Indonesia, 2021)
The purpose of this research is to study cyber crime in e-commerce transactions from the perspective of Islamic criminal law and how to deal with cyber crimes that harm consumers in e-commerce transactions according to the analysis of Islamic criminal law. This research is a normative legal research where laws are conceptualized as written regulations, or laws are conceptualized as rules or norms, the latter being a benchmark for human behavior, and considered appropriate to review written regulations. The results showed that cybercrime is a form of crime in the modern era. Therefore, according to the analysis of Islamic criminal law, cyber crimes can be punished by Ta'zir. For Syrians, ta'zir is a sanction based on disobedience, because it does not explicitly state the crimes contained in the Koran and Hadith.